Plant-protection and biosafety measure in micro-farming - Singh, Narendra; Phour, Manisha; Maurya, Samar (Indian Farming, 2018)
Every micro-farming fellow should be aware of the sources of pathogens for each crop grown in their particular operation and should plan to eliminate those sources of disease to the greatest extent possible. The fungal infection is common disease problem in micro-farming during 2 to 5 days after sowing. The Rhizopus species are relatively mild pathogen that require environmental conditions that favour infection.